Gender Discrimination and National Politics: The Nigerian Case - Azuh, PhD, Dominic; Egharevba, PhD, Matthew D.; E. Azuh, Akunna (Covenant University Journal of Politics and International Affairs, 2016)
Women participation in Nigerian politics is crucial to the development of Nigeria and since women constitute a sizeable proportion of the population, neglecting them may mean losing their valuable contribution. Traditional socio-economic and political and cultural structures aid discrimination against women leading to loss of contributions of women to societal development. Raising the status of women through gender empowerment has is considered in certain quarters as vital in the quest towards improvement in living standards and wellbeing of the masses in economies transiting to stability. Despite global efforts to improve the poor conditions of women through numerous conventions and conferences such as CEDAW, MDGs among others, gender discrimination has not ceased. The paper aims at throwing light on gender discrimination, obstacles to gender equality and suggests strategies for promoting effective gender equality and empowerment of women. Using secondary data, from the Nigerian Bureau of Statistics, the paper found that gender discrimination exists in all variable indicators considered. Current status of Nigerian women in relation to men in the areas of education, income, labor force and share of seats in parliament or level of political participation were considered. Some of the main factors militating against women’s effective participation in politics are illiteracy, poverty, money politics, instrument of intimidation, harmful traditional practices and discriminatory cultural stereotypes, violence against women, barriers by electoral process, and religious barriers. It is suggested that more efforts are required by civil society groups and government agencies for greater awareness on gender issues and rekindling efforts of all stakeholders in the quest to formulating policies and programs towards reduction of gender inequality.